2013
DOI: 10.1021/np3008655
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Elucidation, and Iron-Binding Properties of Lystabactins, Siderophores Isolated from a Marine Pseudoalteromonas sp.

Abstract: The marine bacterium Pseudoalteromonas sp. S2B, isolated from the Gulf of Mexico after the Deepwater Horizon oil spill, was found to produce lystabactins A, B, and C (1−3), three new siderophores. The structures were elucidated through mass spectrometry, amino acid analysis, and NMR. The lystabactins are composed of serine (Ser), asparagine (Asn), two formylated/hydroxylated ornithines (FOHOrn), dihydroxy benzoic acid (Dhb), and a very unusual nonproteinogenic amino acid, 4,8-diamino-3-hydroxyoctanoic acid (Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The UV spectroscopic analysis of ferric-albisporachelin complex indicates that the typical hydroxamate coordinating groups are presented in the complex, implied by the broad absorption band at about 440 nm (SI, Figure S22 ). These results indicated that the hydroxamate moieties are involved in iron binding [ 7 ], which was in accordance with the albisporachelin structure.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The UV spectroscopic analysis of ferric-albisporachelin complex indicates that the typical hydroxamate coordinating groups are presented in the complex, implied by the broad absorption band at about 440 nm (SI, Figure S22 ). These results indicated that the hydroxamate moieties are involved in iron binding [ 7 ], which was in accordance with the albisporachelin structure.…”
Section: Resultssupporting
confidence: 68%
“…Albisporachelin was hydrolyzed with HI (Hydrogen iodide) and the resulting amino acids were derivatized with N α-(5-fluoro-2,4-dinitrophenyl)- l -alaninamide ( l -FDAA). Hydrolysis with HI provides the additional advantage of reducing hydroxylamines [ 7 , 10 , 14 ]. The derivatized hydrolysates were then compared with amino acid standards derivatized with l -FDAA or d -FDAA using LC/MS ( Figures S15–S21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three unusual siderophores, lystabactins A–C ( 78 – 80 ), were obtained from the marine bacterium Pseudoalteromonas sp. S2B [64]. In order to further determine their stability by chelating Fe(III), the pFe scale was used to compare with the iron-binding stability of siderophores.…”
Section: Diversity Of Siderophores From Marine Microorganismsmentioning
confidence: 99%
“…Examples are aerobactins, amphibactins, ochrobactins, marinobactins, aquachelins, lystabactins, rhodobactins and amychelins among others ( Fig. 5; Dhungana et al 2007;Neilands 1995;Seyedsayamdost et al 2011;Zane and Butler 2013).…”
Section: Siderophore Coordination Groupsmentioning
confidence: 99%